Respuesta :

Answer:

[tex]{f}^{ - 1} (f(93)) = 93[/tex]

[tex]f(f(7)) = - 15[/tex]

Step-by-step explanation:

A function and its inverse has the following properties

[tex] {f}^{ - 1} (f(x)) = x[/tex]

This implies that;

[tex] {f}^{ - 1} (f(93)) = 93[/tex]

From the table,

[tex]f(7) = - 6[/tex]

This means that:

[tex]f(f(7)) = f( - 6)[/tex]

[tex]f(f(7)) = - 15[/tex]

Note that: f(7) means the value of f(x) when x=7.

From the table f(x)=-6 when x=7.

That is why f(7)=-6.

Answer:

93

-15

Step-by-step explanation: